Bye-Graine : desarrollo e investigación de un dispositivo encargado de tratar y prevenir la migraña (2020)
Migraine is a disease characterized by a severe headache that can be accompanied by dizziness, photosensitivity and in the most severe cases nausea and vomit. It affects around 280 million people worldwide and about 7 million people in Colombia. In addition, drug treatments are mostly harmful to patients that use them for a prolonged period of time, adding to their loss of effectiveness. Therefore, this project sought to develop a way to treat migraine episodes in women between the age of 18 and 25 to reduce the frequency and duration of migraine. Once the approach was chosen, it was imperative to talk to specialists and continue the bibliographic search. As a result, the proposed solution was a noninvasive, affordable and side-effect-free neuromodulation device to treat common migraine symptoms. In this order of ideas, different prototypes were designed for this device in terms of the shape, stimulation methodology and electrical components of the device. In addition, a complete business model was developed for the device and the financial viability of the device was corroborated. The net result of the project was a functional device which is currently ready for the initiation of preliminary trials in patients. The device action plan, preliminary tests and final iterations of the device are currently being prepared.